Challenges to Building Scalable Services: A Survey of Microsoft's Internet Services - Hunt, Galen; Levi, Steven (Microsoft Research, 2015)
This paper was originally circulated as a Microsoft Confidential memo in fall 1999. Its purpose was to document the findings of the co-authors as we attempted to understand the state-of-the-art of large internet services. Our original intent was to gather the data documented in this paper purely for our own to understand. However, as we discussed early findings with our colleagues, we quickly realized the value of circulating them to a wider audience. The original memo was circulated to Microsoft’s entire executive staff, at Bill Gates’ request, and quickly passed around. For file server data, we believe over 1,000 MS employees read the original memo in the first three months after internal publication. In the 15 years since this paper’s circulation, much has changed at Microsoft and in the industry. Experience gathered in writing this paper directly lead to our discovery of the core principles of what is now widely known as cloud computing. In 1999, Microsoft’s largest internet service had just over 2,000 computers. Today, many cloud services use over 100,000 servers. Many of the services and technologies described in this paper no longer exist. Those that remain have morphed beyond recognition under the intense pressure of growing by orders of magnitude.